Neuropatia laríngea recorrente grau IV em equino: relato de caso - Cesário, Bruna Castro (Universidade Federal Rural do Semi-Árido, 2021)
Respiratory disorders are the second leading cause of economic losses in equine farming. Equine laryngeal hemiplegia is highlighted among the frequent respiratory diseases. This study aimed to describe mandatory supervised internship activities and report a case of recurrent grade IV laryngeal neuropathy in equine, followed up during this activity. This was carried out at the large animal clinic at HOVET-UFERSA, where 63 animals were treated, including clinical and surgical cases. Amidst this diversity, the chosen patient was a horse, female, Quarter Horse, gray, 4 years old, 540 kg, used in vaquejada, with a history of equine adenitis, history and clinical signs of progressive fatigue and respiratory noise during and after the work. The presumptive diagnosis was laryngeal hemiplegia, confirmed by endoscopy. Treatment was with the technique of prosthetic laryngoplasty plus ventriculocordectomy. Given the reserved prognosis for athletic performance and the risk of future complications, the patient remains monitored. Laryngeal hemiplegia is a neuropathy of the recurrent laryngeal nerve, usually left, which atrophies the intrinsic muscles of the larynx, causing progressive loss of abduction and adduction of the arytenoid cartilage, limiting airflow in the airways. The internship was of great value to add experience in future professional life. The case reported enabled an in-depth study of this condition and practical follow-up. It is possible to infer the importance of avoiding predisposing factors, performing a clinical examination prior to purchase and endoscopic examination, for a definitive diagnosis and establishment of the recommended treatment.
Keywords: Cartilagens aritenoides; Laringoplastia; Hemiplegia laríngea; Sistema respiratório; Ventriculocordectomia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA